Union of the Comoros : 2019 Article IV Consultation-Staff Report; Press Release. (IMF Staff Country Reports; Country Report ;, 2020)
Economic developments over the past two years have been challenging due mainly to adverse impacts of political uncertainty (constitutional referendum in mid-2018 and elections in early 2019) and Cyclone Kenneth (April 2019), notwithstanding the provision of Fund emergency financial support following the cyclone.